CHLORIDE RESISTANCE OF NANO-PARTICLE REPAIRED CONCRETE - Rostislav Šulc; Michal Himmel; Jiří Němeček (Acta Polytechnica CTU Proceedings)
This paper describes the results of the experimentally modeled chloride ion penetration into different quality concrete structures with fully developed carbonation. Parts of concrete samples were further treated, to increase the resistance of concrete to chloride ion penetration, with a colloidal solution of Nano-silica or solution of Sodium Methyl Siliconate. Measurement of chloride profiles was performed on samples subjected to free diffusion of Cl− ions and on samples subjected to accelerated tests. The chloride ion profile in the samples was determined in layers of 5mm thickness up to a total of 45 mm.